Experimental Analysis of Residual Stress and Bending Strength of Gear Tooth Surface after Shot Peening Treatment. (10th June 2020) - Liang, Dong; Meng, Sheng; Chen, Yi; Hua, Chengli
Abstract : The fatigue strength of a gear tooth surface is affected by various factors, which subsequently impacts the transmission performance of gears. Usually, shot peening treatment is carried out during processing to improve the performance of gears. Most current studies focus on theoretical descriptions and simulation analyses of shot peening treatment. However, in this paper, the relationships among shot peening treatment, residual stress, and bending fatigue strength of a gear tooth surface are discussed, through experimental methods. Based on X-ray stress analysis, at select locations on the test samples, the residual stresses on gear tooth surfaces with and without shot peening treatment are determined and contrasted. The results show that shot peening treatment can effectively increase the residual stress on gear tooth surfaces. In addition, an electromagnetic resonance fatigue tester is used to analyze the bending fatigue strength of gear tooth surfaces. The test results indicate that the bending fatigue strength of the gear teeth with shot peening is higher than that of the gear teeth without shot peening. The obtained conclusions lay the foundation for further practical engineering applications of gears.